Negotiated wage increases and the labor market outcomes of low-wage workers: evidence from the Swedish public sector - Institute for Labour Market Policy Evaluation, Uppsala; Eliasson, Tove; Nordström Skans, Oskar (Uppsala, 2014)
"This paper investigates the impact of a collective agreement stipulating a one shot increase in establishment-specific wage levels in a public-sector setting where wages otherwise are set according to individualized wage bargaining. The agreement stipulated that wages should increase in proportion to the number of low-paid females within each establishment. We find that actual wages among incubents responded to the share of females with a wage below the stipulated threshold, conditional on the separate effects of the share of low wage earners, and the share of females. We find clear evidence of path-dependence in wages, covered workers remained on higher wage levels 4 years after the agreement took effect. The increase in wages resulted in a reduced probability of exit among young workers with relatively good grades and a lower frequency of new hires at the establishment level."